Implementation of RSA 2048-bit and AES 256-bit with Digital Signature for Secure Electronic Health Record Application - Sadikin, Mohamad Ali; Wardhani, Rini Wisnu (CommIT (Communication and Information Technology) Journal, 2016)
This research addresses the implementation of encryption and digital signature technique for electronic health record to prevent cybercrime such as robbery, modification and unauthorised access. In this research, RSA 2048-bit algorithm, AES 256-bit and SHA 256 will be implemented in Java programming language. Secure Electronic Health Record Information (SEHR) application design is intended to combine given services, such as confidentiality, integrity, authentication, and nonrepudiation. Cryptography is used to ensure the file records and electronic documents for detailed information on the medical past, present and future forecasts that have been given only to the intended patients. The document will be encrypted using an encryption algorithm based on NIST Standard. In the application, there are two schemes, namely the protection and verification scheme. This research uses black-box testing and whitebox testing to test the software input, output, and code without testing the process and design that occurs in the system.We demonstrated the implementation of cryptography in SEHR. The implementation of encryption and digital signature in this research can prevent archive thievery.